Evaluasi Integrasi Teaching Factory dan Kurikulum Berbasis Industri untuk Meningkatkan Relevansi Pembelajaran Vokasi - Yusma Elda; Ambiyar Ambiyar; Hasan Maksum (Education Achievement: Journal of Science and Research, 2026)
Vocational education plays a strategic role in preparing graduates who possess competencies that align with the needs of industry and the labor market. However, the gap between vocational school graduates’ competencies and industrial requirements remains a challenge, highlighting the need for learning models that strengthen the relevance of vocational education. Teaching Factory (TeFa) and industry-based curricula have been widely implemented to provide authentic learning experiences and improve the alignment between education and industry. This study aimed to evaluate the integration of Teaching Factory and an industry-based curriculum in enhancing the relevance of vocational learning. A descriptive quantitative approach was employed using survey methods supported by field observations. Data were collected from vocational high school students, productive subject teachers, and Teaching Factory managers through questionnaires and structured observations. The evaluation was conducted using the Context, Input, Process, and Product (CIPP) model. The findings revealed that the integration of Teaching Factory and the industry-based curriculum was generally categorized as good across all evaluation components, with Context, Input, Process, and Product scores of 84.5%, 81.2%, 82.7%, and 87.6%, respectively. In addition, indicators of vocational learning relevance showed high achievement in industry alignment, authentic work experience, technical competence, soft skills, and work readiness. The results indicate that the integration of Teaching Factory and industry-based curricula contributes positively to improving vocational learning relevance by strengthening industry-oriented competencies, authentic learning experiences, and students’ readiness to meet workplace demands.